2021
DOI: 10.4103/aian.aian_106_21
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Vessel Wall Imaging in Primary Angiitis of Central Nervous System

Abstract: Background: High-resolution vessel wall imaging (HRVWI) can aid in differentiating the various intracranial vasculopathies, but has been sparingly used in the diagnosis of primary angiitis of central nervous system (PACNS). This study is aimed to describe the vessel wall imaging characteristics of PACNS. Materials and Methods: Patients with confirmed diagnosis of PACNS according to the Calabrese and Mallek criteria who had abnormal HRVWI were included in this retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
0
0
3
Order By: Relevance
“…It was useful in the detection of medium vessel vasculitis subtype, distinguishing PACNS from mimics, 13 and is another tool that could be used in patients in whom biopsy was not performed or negative. 14 The distinction between small and medium/large vessel vasculitis is not always mutually exclusive but rather represents different ends of a spectrum because the disease process may affect all vessels. Similar patients were also reported by a German cohort.…”
Section: Discussionmentioning
confidence: 99%
“…It was useful in the detection of medium vessel vasculitis subtype, distinguishing PACNS from mimics, 13 and is another tool that could be used in patients in whom biopsy was not performed or negative. 14 The distinction between small and medium/large vessel vasculitis is not always mutually exclusive but rather represents different ends of a spectrum because the disease process may affect all vessels. Similar patients were also reported by a German cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Более того, тяжесть заболевания и скорость прогрессирования могут сильно различаться среди пациентов, что увеличивает неспецифичность клинических проявлений. У большинства пациентов отмечались одновременно несколько симптомов и синдромов [8,21,[28][29][30][31].…”
Section: критерии постановки и клиническая картина пвцнсunclassified
“…В свою очередь, практическое применение МРА и КТА при поражении мелких сосудов невозможно из-за отсутствия изменений на ангиограммах. Поэтому данные методы имеют низкую специфичность, чем использование традиционной контрастной церебральной ангиографии [8,30,42].…”
Section: нейровизуализацияunclassified
See 1 more Smart Citation
“…Sundaram et al found that HRVWI was able to detect distinctive vessel wall appearances, specifically concentric vessel wall thickening and enhancement, yielding abnormalities in 95.2% of the patients in the study. Consequently, this suggested that HRVWI may be considered in the future as a non-invasive diagnostic modality for PACNS and possibly other SVDs [43].…”
Section: Other Diagnostic Modalitiesmentioning
confidence: 99%